(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Today availabilityof e-resources in a university library is very common. But their proper andmaximum use is a matter for discussion. The present paper examines theexistence of various e-resource databases in Library and Information centre.The study also highlights the preferences and importance of online resourcesamong the teachers and research scholars.